Powrót do ruin. O atrakcyjności niemieckiego powojnia - Gortat, Jakub (Załącznik Kulturoznawczy, 2023)
Return to the Ruins: The Appeal of Post-War Germany One of the most important dates in Germany’s postwar history was May 6, 1955, when the Federal Republic joined the North Atlantic Alliance, an event which perfectly reflected the dynamics of geopolitical changes that had taken place in the ten years since the end of World War II. The article focuses on the depictions of the German civilian population in selected motion pictures which, at least in theory, do not hold ordinary Germans responsible for war crimes. A look at the German war-torn landscape and its functionality will play an important role in the analysis, as it is against this background that the key plot lines are developed. Emphasis is placed on the allegorical and metaphorical significance of the ruins and their hidden meanings. The films under investigation are works created independently of German cinematography (except for two recent international co-productions). This is because the purpose of the analysis is to present the changing attitudes of filmmakers representing nations hostile to Germany until 1945 to the civilian population of ruined German cities. These attitudes, it is worth emphasizing, sometimes stand in opposition to the prescribed perception of Germany and Germans resulting from Cold War political realities and dictating that the nation be treated with sympathy, trust, friendship, and love as a new ally.